A case of atheroembolic renal disease: Not uncommon but underdiagnosed (Indian Journal of Case Reports, 2026)
Atheroembolic renal disease (AERD) is the renal component of the more generalized cholesterol embolization syndrome (CES) that results from rupture of the cholesterol-rich plaques in the larger arteries. Most cases are iatrogenic following invasive intravascular procedures, and >25% occur spontaneously. Cholesterol emboli that lodge distally cause ischemia, inflammation, and end-organ damage. We report a 60-year-old male diabetic, hypertensive with cardiovascular problems, presenting with rapidly worsening renal failure following an angiogram. Renal biopsy confirmed AERD associated with inflammation. He showed a very good response to a course of steroids. AERD, though a common problem, remains largely underdiagnosed. Recent years have seen a rise in the incidence, probably due to an increase in the atherosclerosis risk factors and more patients undergoing invasive intravascular procedures. A high index of suspicion is needed for timely diagnosis, as some of them show a good response to steroids.